Research hotspots and trends of acupoint and pain based on PubMed: a bibliometric analysis - Wu, Zhulin; Tan, Wanjun; Li, Siyi; Zhang, Weiqing; Lai, Mingbo; Luo, Weijun (Frontiers in Neurology, 2025)
ObjectiveAcupoint-related interventions are the widely utilized modalities in traditional Chinese medicine for the alleviation of pain. This study aims to identify research hotspots and trends by conducting a bibliometric analysis of the relevant literature on acupoint and pain, thereby elucidating future research directions in this field.MethodA comprehensive search was conducted on PubMed for literature pertaining to acupoint and pain from January 2010 to August 2024. Subsequent bibliometric analyses, encompassing statistical evaluation of bibliographic data, keyword cluster analysis, and co-occurrence analysis, were conducted utilizing the Medpulse database and the Bibliometrix R-package.ResultsA total of 742 articles from 179 journals were included in the analysis, with the majority focusing on complementary and alternative medicine or comprehensive research. The number of publications in this field has shown a consistent annual increase, involving contributions from 19 different countries of corresponding authors. China had the greatest contribution with 407 articles followed by Korea with 25 articles. The leading institutions in terms of publication volume are Chengdu University of Traditional Chinese Medicine, China Medical University, and Kyung Hee University. The topics covered in these articles include acupuncture, transcutaneous electrical acupoint stimulation (TEAS), randomized controlled trials, analgesia, zusanli (st36), systematic review, and anxiety, among others. The main cluster themes are intervention methods for various acupoints and the assessment of their efficacy.ConclusionThe bibliometric analysis has identified the intervention methods of acupoints and the evaluation of their efficacy in pain management as emerging research focal points. Additionally, anxiety is anticipated to emerge as a future research direction within this domain.